Picturesque India : sketches and travels of Thomas and William Daniell - Mahajan, Jagmohan (Lustre Press under arrangement with Rupa & Co., 1983)
Narrative interspersed with reproduction of paintings of Thomas Daniell, 1749-1840, and William Daniell, 1769-1837, British landscape artists.